Scrum Testing With Backlog Management in Agile Development Environment - Harichandan, Suchismita; Panda, Namita; Acharya, Arup Abhinna (International Journal of Computer Sciences and Engineering, 2014)
Recent research report shows the wide acceptance of agile development methodology to create qualitative software in short development cycles. It encourages the early development of software with more promising quality. Early testing strategies with multiple test cycle decrease the number of defect in product. In each iteration automated testing minimize the test effort and cost of testing. Basic agile practices like pair programming, continuous integration, small release, simple design and re-factoring make the development procedure more promising. Scrum is most widely used agile framework for developing software within four weeks. It keeps the document light and manage requirements in the form of product backlog. Testing is performed on the features which are developed in scrum process. Tester are more integrated with development team and collaborate with customers for early feedback. Automated tools are used to enhance the communication in distributed team members. Planning and meetings are the heart of agile testing. Design is more flexible to accommodate change in requirements. Testing process includes unit, integration and regression testing with non functional testing. Automated tool s are used for unit and regression testing in scrum process. These tools helped significantly to simplify and speed up the development cycle. In this paper the testing process performed in scrum environment is discussed through testing model. Test strategies like unit and regression testing method is adopted in the process. Management of user requirements through product backlog and sprint backlog is discussed with suitable example. Different methodology of backlog estimation i.e initial estimation technique and planning poker method is discussed in this paper.